Platypnea-Orthodeoxia Syndrome: A Rare Cause of Hypoxia - Emily Strickland; Zachary Kerosky; Joseph Krivda; Takor Arrey-Mbi (Annals of Internal Medicine: Clinical Cases)
A 23-year-old woman with a history of surgically repaired pulmonary atresia and subsequent severe tricuspid, pulmonic regurgitation, and obesity class II (body mass index, 37.5 kg/m2) presented with 4 months of unexplained hypoxemia and dyspnea that began after an uncomplicated laparoscopic cholecystectomy. Further evaluation found hypoxia in the upright position that promptly resolved in the supine position consistent with platypnea-orthodeoxia syndrome. She was found to have a patent foramen ovale that was percutaneously closed with resolution of symptoms. Platypnea-orthodeoxia syndrome incited by laparoscopic abdominal surgery has been rarely reported in literature, but should be considered in the differential of postoperative dyspnea.